Objetos Mehinako: entre o rito, a retribuição e o mercado - Braida, Roberta Garcia Anffe (2012)
This thesis is an ethnographic study about the Mehinako, Aruak group of Xingu s Indigenous Land, analysing the use and circulation of their material goods. These objects run through a diversity of exchanges, sometimes as offerings, other times as merchandise. From the ethnographic description, this research intends to understand how these transactions are manifested, making a comparative analysis with the classical notion of offerings and agency and identifying their proximity and distinctions